THE ROLE OF ECOLOGICAL CULTURE IN THE STRUCTURE OF THE PERSONALITY OF A FUTURE MEDICAL WORKER (Innovative professional education, 2025)
The article considers the importance of environmental culture in the structure of the personality of a future medical worker. The author analyzes the main components of environmental awareness, their relationship with professional activities in the field of medicine and the impact on the quality of medical services. Particular attention is paid to the integration of environmental culture into the process of training future medical workers, which will contribute to the formation of a responsible attitude towards the environment and human health. The article also highlights the role of environmental education in the professional development of doctors and its importance for the sustainable development of the health care system
Keywords: environmental culture, medical education, professional training, environmental awareness, ethics, sustainable development